Short-term repeatability and postprandial effect assessment of liver perfusion quantification in healthy subjects using arterial spin labeling MRI - Ren, Pengling; Ma, Xia; Liu, Yawen; Zhu, Jinxia; Sun, Yi; Kuehn, Bernd; Yang, Zhenghan; Qiao, Penggang; Wang, Rui; Wang, Zhenchang (Insights into imaging, 2025)
Objectives To assess the stability of liver perfusion quantification using arterial spin labeling MRI (ASL-MRI) in healthy subjects. Materials and methods The arterial and portal venous liver perfusion were measured with two pseudo-continuous ASL acquisitions at a 3.0-Tesla MRI system. To assess the short-term repeatability of ASL-MRI, twelve healthy subjects underwent three consecutive ASL examinations in the fasting state. Following meal ingestion, the postprandial liver perfusion was measured. Changes in liver perfusion measured by ASL before and after meal ingestion, and their correspondence with portal vein hemodynamic variations assessed by Doppler ultrasonography (US), were analyzed to evaluate the stability of ASL in detecting postprandial perfusion alterations. Results The arterial and portal venous liver perfusions in healthy volunteers under the fasting condition were 59.3 ± 17.8 and 237.6 ± 71.9 mL/100 g/min, respectively. Both the arterial and portal venous liver perfusion results demonstrated excellent short-term repeatability (ICCs, 0.97, 0.96; CVs, 6.43%, 6.17%). Furthermore, Bland–Altman plots indicated a high degree of consistency between every two pairs of the three measurements. Compared to the fasting state, the relative changes in postprandial portal venous perfusion measured by ASL-MRI demonstrated a moderate correlation (Pearson correlation coefficient r = 0.66) and good agreement (with all data points in the Bland–Altman plot falling within the limits of agreement) with those in portal vein blood flow measured by Doppler US. Conclusion ASL-MRI enables reliable quantification of liver perfusion in healthy individuals under both constant conditions and altered perfusion state induced by a meal. It holds great promise as a non-invasive tool for diagnosing liver disease. Critical relevance statement The short-term repeatability and postprandial effect of liver perfusion quantification using arterial spin labeling MRI in healthy subjects both exhibited excellent performance, indicating the potential of this technique as a non-invasive tool for diagnosing liver diseases. Key Points Arterial spin labeling (ASL)-MRI enables reliable liver perfusion quantification in healthy individuals. ASL-MRI showed great short-term repeatability for liver perfusion measurement in the fasting state. ASL-MRI and US showed a moderate correlation in measuring postprandial portal venous hemodynamics change. Graphical Abstract